Genome-wide analysis of the mulberry (Morus abla L.) GH9 gene family and the functional characterization of MaGH9B6 during the development of the abscission zone - Deng, Jing; Ahmad, Bilal; Deng, Xuan; Fan, Zelin; Liu, Lianlian; Lu, Xiuping; Pan, Yu; Zha, Xingfu (Frontiers in Plant Science, 2024)
Plant glycoside hydrolase family 9 genes (GH9s) are widely distributed in plants and involved in a variety of cellular and physiological processes. In the current study, nine GH9 genes were identified in the mulberry and were divided into two subfamilies based on the phylogenetic analysis. Conserved motifs and gene structure analysis suggested that the evolution of the two subfamilies is relatively conserved and the glycoside hydrolase domain almost occupy the entire coding region of GH9s gene. Only segmental duplication has played role in the expansion of gene family. Collinearity analysis showed that mulberry GH9s had the closest relationship with poplar GH9s. MaGH9B1, MaGH9B6, MaGH9B5 and MaGH9B3 were detected to have transcript accumulation in the stalk of easy-to-drop mature fruits drop, suggesting that these could play a role in mulberry fruit drop. Multiple cis-acting elements related to plant hormones and abiotic stress responses were found in the mulberry GH9 promoter regions and showed different activities under exogenous ABA and 2,4-D stresses. We found that the lignin content in the fruit stalk decreased with the formation of the abscission zone (AZ), which could indirectly reflect the formation process of the AZ. These results provide a theoretical basis for further research on the role of GH9s in mulberry abscission.